2018
DOI: 10.1021/acsami.8b14026
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Formation of Er0.4Bi1.6O3 Protective Layer at Cobaltite Cathode/Y2O3–ZrO2 Electrolyte Interface under Solid Oxide Fuel Cell Operation Conditions

Abstract: Bismuth based oxides exhibit outstanding oxygen ionic conductivity and fast oxygen surface kinetics and have shown great potential as a highly active component for electrode materials in solid oxide fuel cells (SOFC). Herein, a Nb-doped La0.6Sr0.4Co0.2Fe0.7Nb0.1O3-δ (LSCFNb) electrode with 40% Er0.4Bi1.6O3 (ESB) composite electrode was successfully fabricated by decoration method and directly assembled on barrier-layer-free yttrium stabilized zirconia (YSZ) electrolyte cells, achieving a peak power density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…of Nb-doped La 0.6 Sr 0.4 Co 0.2 Fe 0.7 Nb 0.1 O 3−δ (LSCFNb) electrodes directly assembled on barrier layer-free YSZ electrolyte cells, achieving a peak power density of 1.32 W cm −2 and excellent stability at 750 °C and 250 mA cm −2 for 100 h[303]. Here, these results indicate the redistribution and migration of the ESB phase in the ESB-LSCFNb composite towards the YSZ electrolyte under the influence of cathodic polarization and the formation of a thin ESB layer at the cathode/YSZ electrolyte interface (Fig.19).…”
mentioning
confidence: 99%
“…of Nb-doped La 0.6 Sr 0.4 Co 0.2 Fe 0.7 Nb 0.1 O 3−δ (LSCFNb) electrodes directly assembled on barrier layer-free YSZ electrolyte cells, achieving a peak power density of 1.32 W cm −2 and excellent stability at 750 °C and 250 mA cm −2 for 100 h[303]. Here, these results indicate the redistribution and migration of the ESB phase in the ESB-LSCFNb composite towards the YSZ electrolyte under the influence of cathodic polarization and the formation of a thin ESB layer at the cathode/YSZ electrolyte interface (Fig.19).…”
mentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) at open circuit voltage (OCV) and 1.4 V for the cells is shown in Figure a,b, respectively. From Figure a, all of the cells have a similar ohmic resistance (the first intersection of the X axis (Z′′ = 0)), which consists of the ohmic resistance of the electrolyte, electrodes, leads, and the interfacial contact resistance (mainly resulting from the O 2– transportation between electrode and electrolyte). At OCV, the decrease in R p (the distance between the second intersection and the first intersection of the X axis) after the impregnation of CeO 2 nanoparticles reflects the fact that the impregnated cathode has a stronger ability to adsorb CO 2 , as shown by the results of CO 2 -TPD. In Figure b, the total resistance values (the second intersection of the X axis, R tot ) of the cells after the impregnation of CeO 2 nanoparticles are smaller than for the conventional cathode.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the directly assembled ESB-La 0.6 Sr 0.4 Co 0.2 Fe 0.7 Nb 0.1 O 3− δ (LSCFN) composite electrode has exhibited outstanding ORR performance and stability. 61 It was revealed that cathodic polarization induced the generation of a thin ESB layer at the interface after the stability test, as shown in Fig. 10.…”
Section: Nano-scale Fabrication Techniquesmentioning
confidence: 93%